The Influence of Product Quality, Price, and Online Promotion on Purchasing Decisions - Putri, Made Ari Nadia; Putra, I Putu Iwan Pramana; Purnami, Anak Agung Sri (PT Keberlanjutan Strategis Indonesia, 2026)
The phenomenon that occurs in this study is related to changes in consumer behavior towards digital through the increasingly competitive Shopee e-commerce platform where the consumer response rate is below 70 percent based on 2024 review statistical data, this causes a decrease in sales due to fluctuations, where product quality, price and online promotions are the main determining factors for purchasing decisions, especially at the Orianaeyewear Store. This study aims to determine the effect of product quality, price, and online promotions on purchasing decisions in Shopee e-commerce (case study at the Orianaeyewear Store in Gianyar). The number of populations in this study is not known for certain, therefore the sample in this study was selected using the Hair formula with a total sample of 100 respondents. The data analysis technique used in this study uses multiple linear regression analysis. The results of the study state that product quality, price and online promotions have a significant positive effect on purchasing decisions in Shopee E-commerce (Case Study at the Orianaeyewear Store in Gianyar). Product quality has a positive and significant effect on purchasing decisions in Shopee E-commerce (Case Study at the Orianaeyewear Store in Gianyar). Price has a positive and significant effect on purchasing decisions on Shopee e-commerce (Case Study on Orianaeyewear Store in Gianyar). Online promotions have a positive and significant effect on purchasing decisions on Shopee e-commerce (Case Study on Orianaeyewear Store in Gianyar).